2009
DOI: 10.1258/la.2009.009005
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic effects of oral paracetamol in two strains of mice undergoing vasectomy

Abstract: As the production of transgenic mice increases, the need for vasectomized mice also increases. Currently, there is no accurate method of identifying pain in these mice which can be used routinely and therefore no acceptable analgesic regimens can be established. Sixteen male CBA/CaCrl and 16 male DBA/2JCrl mice were randomly allocated to one of four treatment groups (saline, low, medium and high dose oral paracetamol) and then underwent abdominal vasectomy. Their behaviour was videotaped (filmed) preoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…The frequency of pain-related behaviours assessed using a manual scoring system (composite pain score) showed a similar pattern to that of the MGS and successfully differentiated between both the pre and post-operative periods, and the effects of analgesic treatment compared to control (saline). Those behaviours that have been previously shown to change in response to post-operative pain [4], [5], [16] were highly correlated with the MGS. The animals showing high MGS also exhibited high composite pain scores, high frequencies of wound licking and grooming and low frequencies of rearing.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The frequency of pain-related behaviours assessed using a manual scoring system (composite pain score) showed a similar pattern to that of the MGS and successfully differentiated between both the pre and post-operative periods, and the effects of analgesic treatment compared to control (saline). Those behaviours that have been previously shown to change in response to post-operative pain [4], [5], [16] were highly correlated with the MGS. The animals showing high MGS also exhibited high composite pain scores, high frequencies of wound licking and grooming and low frequencies of rearing.…”
Section: Discussionmentioning
confidence: 75%
“…The study by Langford and colleagues [9] represents the first successful attempt to assess pain via changes in facial expression in any animal species. Post-vasectomy changes in behaviour have been successfully assessed in various mouse strains using both manual and automated behavioural analysis [4], [5], [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations in vasectomised mice have shown that the vasectomy resulted in behavioural changes indicative of pain [18,33,86]. However, conclusions drawn from FCM in relation to vasectomy vary depending on the sampling method [33,86] and how corticosterone levels are expressed [31,43].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increased use of genetically modified mice, vasectomy is a common surgical procedure in laboratory animal facilities. The traditional procedure of vasectomy involves tissue injury and interference of the abdominal cavity and has been shown to result in behavioural changes indicative of pain [18,33,86]. Furthermore, the procedure requires general anaesthesia, which may be a significant stressor for the animals [78].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Use of automated systems not only reduces time constraints but also minimizes observer bias. The validity of this system is based on having been shown to be as effective as manual scoring of mouse behaviour for a range of specific Laboratory Animals 2012; 46: 304 -310…”
Section: Introductionmentioning
confidence: 99%